A hierarchy of selection pressures determines the organization of the T cell receptor repertoire - Mark, Michal; Reich-Zeliger, Shlomit; Greenstein, Erez; Reshef, Dan; Madi, Asaf; Chain, Benny; Friedman, Nir (Frontiers in Immunology, 2022)
We systematically examine the receptor repertoire in T cell subsets in young, adult and LCMV infected mice. Somatic recombination generates diversity, resulting in limited overlap between nucleotide sequences of different repertoires even within the same individual. However, statistical features of the repertoire, quantified by V gene and CDR3 k-mer frequency distributions, are highly conserved. A hierarchy of immunological processes drives evolution of this structure. Intra-thymic divergence of CD4+ and CD8+ lineages, imposes subtle but dominant differences observed across repertoires of all subpopulations in both young and adult mice. Differentiation from naive through memory to effector phenotype imposes an additional gradient of repertoire diversification, which is further influenced by age in a complex and lineage dependent manner. The distinct repertoire of CD4+ regulatory T cells is more similar to naive cells in young mice, and to effectors in adults. Finally, we describe both divergent (naive and memory) and convergent (CD8+ effector) evolution of the repertoire following acute infection with LCMV. This study presents a quantitative framework which captures the structure of the repertoire in terms of its fundamental statistical properties and describes how this structure evolves as individual T cells differentiate, migrate and mature in response to antigen exposure.